PROPOSAL FOR INDICATORS FOR ASSESSING THE BUDGET EFFICIENCY OF SOCIAL SERVICES - Chobanov, Dimitar (E-Journal VFU, 2025)
In recent years, there has been an accelerated rate of growth in social service expenditures. This raises doubts as to whether budget funds are being spent in accordance with the principles of minimum-cost, efficiency, and effectiveness. In its annual reports, the Agency for Quality of Social Services presents some indicators for assessing the budgetary efficiency of social services. However, this assessment is incomplete and additional indicators need to be considered. This article provides a proposal for such indicators for assessing the budgetary efficiency of social services. Based on these indicators, a practical appraisal has been made for the period 2021-2025.
Keywords: Budget Efficiency; Social Services